Submerged membrane filtration process coupled with powdered activated carbon for nonylphenol ethoxylates removal - Phuoc-Dan Nguyen (IWA Publishing, 2021)
A combination of a submerged membrane filtration system and powdered activated carbon (PAC) was investigated for nonylphenol ethoxylates removal. Both filtration flux and initial powdered activated carbon dosage had significant effects on the micropollutants removal efficiency. The best performance was achieved under the filtration flux of 20 L/m2.h and the initial powdered activated carbon of 50 mg/L. The removal efficiencies of nonylphenol ethoxylates was obtained at 75±5% in the first 60 hours, and then decreased at 55±7% and 23±11% in the following hours, respectively. As observed, over 65% of dissolved organic carbon mass adsorbed into powdered activated carbon that was suspended in the bulk phase, and the remainder was adsorbed into powdered activated carbon that deposited on the membrane surface. It reveals that the combination between submerged membrane filtration and PAC could be an effective solution for enhancing removal of micropollutants from water. HIGHLIGHTS Continuous microfiltration coupled with PAC effectively removed nonylphenol ethoxylate.; 75±5% of nonylphenol ethoxylate was rejected after 60 hours of operation.; Removal efficiencies of dissolved organic carbon could reach 53±4%.; Over 65% of dissolved organic carbon mass adsorbed into powder activated carbon.;